Will Herberg, from Right to Right - Ausmus, Harry J. (University of North Carolina Press, 1987)
A study of the life and thought of Will Herberg (1906-1977), a theorist in sociology and religion. A communist in the 1920s-30s, Herberg was identified in the 1950s as a moderate and an advocate of American religious pluralism, and in the 1960s as an anti-communist crusader. On pp. 81-84 shows how, after his abandonment of communism and rediscovery of Judaism, Herberg viewed antisemitism as the inevitable result of the Jew's marginal position in the world and of Judaism's witness to God's message. He contended that Christians who engaged in antisemitism were rebelling against their religion and lapsing into paganism. He condemned Soviet antisemitism and predicted the USSR's adoption of anti-Zionism. He also discussed the reasons for Black antisemitism (pp. 191-194).
Keywords: Biography; Biography; Jewish scholars; Biography; Jews; Herberg; Will; Religion historians; United States; dept.art; faculty_collection

Click, Rumble, Roar: Poems About Machines - Hopkins, Lee Bennett; Audette, Anna Held (T.Y. Crowell, 1987)
A collection of eighteen poems about machines by Myra Cohn Livingston, Eve Merriam, David McCord, and others.
Keywords: Children's poetry; American; Machinery; Juvenile poetry; American poetry; dept.art; faculty_collection